Perfluorinated solid polymer electrolyte material and preparation method thereof

By using polyfluorocyclic acrylate as the backbone of the polymer electrolyte and combining with a solvent system containing fluorine-containing organic solvents, the problem of poor antioxidant performance of polymer electrolytes in the prior art is solved, and the upper limit of the electrochemical window and the improvement of solid-state battery performance is achieved.

CN119674204AActive Publication Date: 2025-03-21WUHAN UNIV OF TECH

Patent Information

Application Number
CN202411422441.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-03-21
Estimated Expiration
2044-10-12

AI Technical Summary

Technical Problem

The existing polymer electrolytes have poor oxidation resistance and are difficult to adapt to high-voltage positive electrode materials, resulting in rapid attenuation of battery capacity.

Method used

Polyfluorocyclic acrylate is used as the polymer backbone of the polymer electrolyte, and polymerized under a solvent system containing lithium salts and fluorine-containing organic solvents to improve the oxidation resistance and ionic conductivity of the electrolyte.

Benefits of technology

The upper limit of the electrochemical window of polymer electrolytes has been significantly improved, from 4.2V to 5.5V, adapting to high-voltage positive electrode materials, and improving the performance and cycle stability of solid-state batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674204A_ABST
    Figure CN119674204A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of lithium ion battery materials and electrochemistry, and particularly relates to a perfluorinated solid polymer electrolyte material and a preparation method thereof. According to the invention, the polyfluorinated cycloacrylate is selected as a polymer skeleton, and the oxidation resistance of the electrolyte is effectively improved by a fluorinated group and a cyclic structure. In addition, the polyfluorinated cycloacrylate skeleton and fluorine-containing solvent molecules have excellent compatibility, and meanwhile, formation of an inorganic-rich interface layer on the surface of an electrode is facilitated, and the deposition form of lithium ions is improved. The perfluorinated solid polymer electrolyte jointly formed by a polyfluorinated cycloacrylate polymer skeleton and fluorine-containing solvent molecules has excellent ionic conductivity (gt; 10 <-3 > S cm <-1 >) and a high antioxidant voltage upper limit (5.5 V).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of lithium ion battery materials and electrochemistry, and specifically relates to a perfluorinated solid polymer electrolyte material and a preparation method thereof. Background Art

[0002] Polymer electrolytes have high ionic conductivity, good flexibility, easy processing, and good contact and adhesion with the interface. They are one of the key materials for effectively improving the safety, energy density and cycle life of lithium-ion batteries. However, the antioxidant properties of polymer electrolytes reported so far are poor, making them difficult to adapt to high-voltage positive electrode materials. There are two main reasons: First, the polymer skeleton in the polymer solid electrolyte will undergo oxidative decomposition under high pressure. Currently, the most commonly used polymer skeleton is based on chain acrylates, such as polyethylene glycol diacrylate (PEGDA) and polyethylene glycol dimethacrylate (PEGDMA). The C=C double bond remaining at the end of conventional chain acrylates after polymerization is easily decomposed under high pressure. The electrochemical window of PEGDA is generally around 4.2V. When paired with NCM high-voltage materials, the electrolyte undergoes severe oxidative decomposition, resulting in rapid decay of the battery capacity. CN 114725504 A discloses a polymer electrolyte, which improves the cycle stability of lithium-ion batteries by introducing functional groups (acrylic phosphate and vinyl siloxane). However, since the problem of easy oxidation of the polymer skeleton has not been effectively solved, the upper voltage limit of the battery cycle is only 4.2V. Second, conventional carbonate solvents have poor stability under high voltages and are easily decomposed to produce a large number of harmful organic components that reduce the electrolyte-electrode interface performance, ultimately affecting the cycle life of the battery. By introducing a strongly electronegative fluorine atom group, the electrochemical stability of the electrolyte under high pressure can be effectively improved. Therefore, in order to solve the practical problems of the above-mentioned existing polymer electrolytes, a polymer electrolyte with simple preparation process, high ionic conductivity, excellent antioxidant performance and low interface impedance is developed, which can be matched with high-voltage positive electrode materials. Summary of the invention

[0003] The technical problem to be solved by the present invention is to provide a perfluorinated solid polymer electrolyte material and a preparation method to improve the anti-oxidation performance and ionic conductivity of the perfluorinated polymer electrolyte, and to apply it to batteries with NCM811 as the positive electrode to achieve stable circulation under 4.5V high voltage and improve the performance of solid-state batteries.

[0004] In order to achieve the above technical objectives, the present invention adopts the following technical solutions:

[0005] The present invention provides a perfluorinated polymer electrolyte material, which is obtained by initiating polymerization of a polyfluorinated cyclic acrylate monomer in a solvent system containing a lithium salt and a fluorinated organic solvent. The structural formula of the polyfluorinated cyclic acrylate monomer is shown in formula (I):

[0006]

[0007] In formula (I): R1 is selected from H, methyl, ethyl or propyl;

[0008] R2 is selected from a benzene ring or a cyclic group containing a fluorine atom as shown in formula (II):

[0009]

[0010] According to the above scheme, the polyfluorinated cyclic acrylate monomer is selected from one or more of 3-(2,4-difluorophenyl)methyl acrylate, 2,4,6-trifluorobenzyl methacrylate, 2,3,5,6-tetrafluorobutyl acrylate, pentafluorobenzyl methacrylate, perfluorocyclohexyl methacrylate and the like.

[0011] According to the above scheme, the fluorine-containing organic solvent is selected from fluorocarbonate compounds, and specifically preferably at least one of fluoroethylene carbonate (FEC), bisfluoroethylene carbonate (DFEC), methyl trifluoroethyl carbonate (FEMC), bis (2,2,2-trifluoroethyl) carbonate (TFEC), and ethyl trifluoroethyl carbonate (ETFEC).

[0012] According to the above scheme, the content of the polyfluorinated cyclic acrylate monomer is 3-15wt% of the total weight of the lithium salt and the fluorine-containing organic solvent.

[0013] The present invention provides a method for preparing a perfluorinated polymer electrolyte material, wherein components including a polyfluorinated cyclic acrylate group, a lithium salt, and a fluorinated organic solvent are uniformly stirred to obtain a precursor solution, and the precursor solution is subjected to a thermal polymerization reaction under the action of an initiator to obtain a polymer electrolyte containing a polyfluorinated cyclic acrylate group, and the method specifically comprises the following steps:

[0014] 1) dissolving a lithium salt in an organic solvent under an argon protective atmosphere to obtain a mixed solution;

[0015] 2) Adding a polyfluorocyclic acrylate monomer to the mixed solution obtained in step 1); .

[0016] 3) Adding an initiator to the mixed solution obtained in step 2) and dispersing the mixture uniformly to obtain a precursor solution.

[0017] 4) Heating at a certain temperature until the polymerizable monomers are completely polymerized to form a polymeric electrolyte. The conditions for the thermally initiated polymerization reaction are: a polymerization temperature of 40 to 80° C. and a polymerization time of 6 to 60 hours.

[0018] According to the above scheme, the lithium salt is selected from lithium hexafluorophosphate (LiPF6), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium tetrafluoroborate At least one of lithium difluorooxalatoborate (LiDFOB) with a concentration of 0.5-3 mol / L.

[0019] According to the above scheme, the initiator is selected from azobisisobutyronitrile (AIBN), azobisisoheptanenitrile (C 14 H 24 N4), the content of which is 0.3-1 wt % of the total weight of the polyfluorocyclic acrylate monomer, the lithium salt and the fluorine-containing organic solvent.

[0020] The present invention provides a perfluorinated solid polymer electrolyte prepared by the above preparation method.

[0021] The present invention further provides the use of the above-mentioned perfluorinated polymer electrolyte as a lithium ion battery electrolyte material for assembling a lithium ion battery.

[0022] According to the above scheme, the above assembly method is: according to the assembly method of liquid lithium battery, the obtained precursor solution is dripped into the diaphragm, and the battery is assembled with the positive electrode and the negative electrode, left to stand, and then heated at a certain temperature, until the polymerization monomer is completely polymerized and a polymer electrolyte is formed inside the battery, that is, a fully fluorinated solid polymer electrolyte lithium battery is obtained, wherein: the conditions of the thermally initiated polymerization reaction are: the polymerization temperature is 40 to 80°C, and the polymerization time is 6 to 60 hours.

[0023] According to the above scheme, the lithium-ion battery is a Li||NCM811 battery or a LiFePO4||Li battery.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] 1. The present invention selects polyfluorinated cyclic acrylate as the polymer skeleton of the perfluorinated polymer electrolyte. The fluorinated group and the cyclic structure effectively improve the oxidation resistance of conventional acrylates. Combined with the use of fluorinated organic solvents, the upper limit of the electrochemical window of the polymer electrolyte is increased from 4.2V to 5.5V, so that the acrylate polymer electrolyte can be adapted to high-voltage application scenarios such as NCM811 as the positive electrode, thereby improving the performance of solid-state batteries.

[0026] 2. The polyfluorinated cyclic acrylate skeleton provided by the present invention has excellent compatibility with fluorinated organic solvent molecules, which is conducive to forming an inorganic-rich interface layer on the electrode surface and improving the deposition morphology of lithium ions. The perfluorinated solid polymer electrolyte formed by the polyfluorinated cyclic acrylate polymer skeleton and fluorinated solvent molecules has excellent ionic conductivity (>10 -3 S cm -1 ). The material design and preparation of the present invention are simple, controllable and practical, and provide a new idea for preparing perfluorinated polymer electrolytes and related batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 Comparison of ionic conductivity between perfluorocyclohexyl methacrylate electrolyte (F-GPE) and PEGDA-based electrolyte (GPE).

[0028] Figure 2 It is an electrochemical window for perfluorocyclohexyl methacrylate electrolyte and PEGDA-based electrolyte.

[0029] Figure 3 The lithium battery is assembled with the ternary material NCM811 as the positive electrode and perfluorocyclohexyl methacrylate electrolyte, and an electrochemical floating test is conducted in the voltage range of 4.2V-4.8V.

[0030] Figure 4 The lithium battery is assembled with the ternary material NCM811 as the positive electrode and a PEGDA-based electrolyte, and an electrochemical floating test is performed in the voltage range of 4.2V-4.8V.

[0031] Figure 5 The lithium-copper battery was assembled using perfluorocyclohexyl methacrylate-based electrolyte and PEGDA-based electrolyte. -2 Morphology and cross-sectional view of lithium deposition on the copper foil surface after discharge for 5 h at a current density of .

[0032] Figure 6 The lithium iron phosphate (LiFePO4) is used as the positive electrode, and the perfluorocyclohexyl methacrylate-based electrolyte and the PEGDA-based electrolyte are used to assemble the lithium battery. The voltage range is 2.5V to 4V at a rate of 1C (1C = 170mAh g -1 ) cycle performance diagram.

[0033] Figure 7 The lithium battery is assembled with ternary material NCM811 as the positive electrode, using perfluorocyclohexyl methacrylate-based electrolyte and PEGDA-based electrolyte. The battery is charged at a rate of 0.2C (1C = 200mAh g) in the voltage range of 3V to 4.5V. -1 ) cycle performance diagram.

[0034] Figure 8 The lithium battery is assembled with ternary material NCM811 as the positive electrode and perfluorocyclohexyl methacrylate-based electrolyte. The battery is charged at a rate of 0.2C (1C = 200 mAh g) in the voltage range of 3V to 4.5V. -1 ) Cyclic capacity-voltage diagram.

[0035] Fig. 9 It is the ionic conductivity of the polymer electrolyte (F1-GPE) prepared with 5 wt% perfluorocyclohexyl methacrylate monomer.

[0036] Fig.10 The lithium battery is assembled with lithium iron phosphate (LiFePO4) as the positive electrode and a polymer electrolyte (F1-GPE) prepared with 5wt% perfluorocyclohexyl methacrylate monomer. The battery can be charged at a rate of 1C (1C = 170 mAh g) in a voltage range of 2.5V to 4V. -1 ) cycle performance diagram.

[0037] Fig.11 The lithium battery is assembled with the ternary material NCM811 as the positive electrode and a polymer electrolyte (F1-GPE) prepared with 5wt% perfluorocyclohexyl methacrylate monomer. The battery is charged at a rate of 0.2C (1C = 200mAh g) in the voltage range of 3V to 4.5V. -1 ) Cyclic capacity-voltage diagram. DETAILED DESCRIPTION

[0038] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.

[0039] Example 1

[0040] A preparation method and application of a perfluorinated polymer electrolyte and a solid-state battery, which are prepared by the following steps:

[0041] 1) Weigh 0.5 mL of FEC and 0.5 mL of FEMC solvent and mix them evenly, add 0.2871 g of LiTFSI (1 M) and stir evenly.

[0042] 2) Add 8 wt% of the total weight of lithium salt and fluorine-containing organic solvent to the mixed solution, stir for 2 hours, then add 0.3 wt% of initiator AIBN, stir for 30 minutes to obtain a precursor solution.

[0043] 3) According to the assembly method of liquid lithium battery, the obtained precursor solution was added dropwise to the polypropylene (PP) separator, and the button battery was assembled. The button battery was left to stand for 2 hours, and then the battery was heated at 60°C for 12 hours to finally obtain a fully fluorinated polymer electrolyte lithium battery, and the fully fluorinated polymer electrolyte was named F-GPE.

[0044] Figure 1 This is a comparison of the ionic conductivity of perfluorocyclohexyl methacrylate-based electrolyte (F-GPE) and PEGDA-based electrolyte (GPE). The preparation of perfluorocyclohexyl methacrylate-based electrolyte and PEGDA-based electrolyte uses the same fluorinated solvent, lithium salt, initiator, and the synthesis conditions are the same. It can be found that the bulk resistance of perfluorocyclohexyl methacrylate-based electrolyte (3.2Ω) is lower than that of ordinary PEGDA-based electrolyte (6.3Ω). The ionic conductivity of perfluorocyclohexyl methacrylate-based electrolyte is calculated to be 3.93×10 -3 S / cm, while the ionic conductivity of common PEGDA-based electrolytes is 1.72×10 -3 S / cm. This indicates that the perfluorocyclohexyl methacrylate-based electrolyte has excellent ion transport properties.

[0045] Figure 2 It is the electrochemical window of perfluorocyclohexyl methacrylate-based electrolyte (F-GPE) and PEGDA-based electrolyte (GPE). It can be found that the electrochemical window of PEGDA-based electrolyte is significantly improved to 4.6V due to the introduction of fluorinated solvent, while the electrochemical window of perfluorocyclohexyl methacrylate-based electrolyte can be increased to 5.5V. This shows the excellent stability of polyfluorinated cycloacrylate-based electrolyte in high voltage resistance.

[0046] Figure 3 and Figure 4 The ternary material NCM811 was used as the positive electrode, and the lithium battery was assembled using a polyfluorinated cyclic acrylate-based electrolyte (F-GPE) and a PEGDA-based electrolyte (GPE), respectively, and an electrochemical floating test was performed in the voltage range of 4.2V-4.8V. It further reflects the high-voltage stability of solid electrolytes in practical applications. It was found that the Li||NCM811 battery with a perfluorocyclohexyl methacrylate-based electrolyte still has a stable leakage current in the voltage range of 4.2V-4.8V. In sharp contrast, the battery using a PEGDA-based electrolyte was charged to 4.4V at a constant voltage, and the current increased dramatically and jittered. These results further indicate that the oxidative stability of polyfluorinated cyclic acrylate-based electrolytes is significantly enhanced.

[0047] Figure 5 The Li-Cu battery was assembled using polyfluorinated cyclic acrylate-based electrolyte (F-GPE) and PEGDA-based electrolyte (GPE).-2 The morphology and cross-sectional view of lithium deposition on the copper foil surface after discharge at a current density of 5 h. It can be observed that the lithium deposited on the copper foil surface using perfluorocyclohexyl methacrylate-based electrolyte is densely arranged and flat and uniform, without obvious needle-shaped lithium dendrites, indicating that this electrolyte is conducive to Li + The uniform distribution of flux and the regulation of lithium nucleation ultimately promote the uniform deposition of Li, with excellent lithium deposition kinetics, which can effectively suppress lithium dendrites. However, a large number of loose and porous needle-shaped lithium dendrites are deposited on the surface of copper foil using PEGDA-based electrolyte, indicating that serious side reactions occur between lithium metal and electrolyte, forming a large amount of dead lithium.

[0048] Figure 6 The lithium battery is assembled with lithium iron phosphate (LiFePO4) as the positive electrode and lithium metal as the negative electrode, using polyfluorinated cyclic acrylate-based electrolyte (F-GPE) and PEGDA-based electrolyte (GPE). The battery is charged at a rate of 1C (1C = 170 mAh g) in the voltage range of 2.5 V to 4 V. -1 ) is a cycle performance diagram. It can be found that after using perfluorocyclohexyl methacrylate-based electrolyte, its initial discharge specific capacity is 138.6 mAh g -1 , which is slightly higher than the initial discharge capacity of the PEGDA-based electrolyte, which is 127.6 mAh g -1 . And the cycle performance of perfluorocyclohexyl methacrylate-based electrolyte is more stable.

[0049] Figure 7 The lithium battery is assembled with ternary material NCM811 as the positive electrode and lithium metal as the negative electrode, using polyfluorinated cyclic acrylate-based electrolyte (F-GPE) and PEGDA-based electrolyte (GPE). The battery is charged at a rate of 0.2C (1C = 200 mAh g) in the voltage range of 3V to 4.5V. -1 ) is a cycling performance diagram. It can be found that the initial discharge capacity of the battery using PEGDA-based electrolyte is 81.1 mAh g -1 At the 20th cycle, the discharge capacity rapidly decreased to 3.1 mAh g -1 The initial discharge capacity of the battery using polyfluorinated cyclic acrylate-based electrolyte is 184.3 mAh g -1 After 20 cycles, the discharge capacity is 187.2 mAh g -1 , there is no capacity loss.

[0050] Figure 8 The lithium battery is assembled with ternary material NCM811 as the positive electrode and polyfluorinated cyclic acrylate-based electrolyte (F-GPE). The battery is charged at a rate of 0.2C (1C = 200 mAh g) in the voltage range of 3V to 4.5V. -1) cycle specific capacity-voltage diagram. This shows that the perfluorocyclohexyl methacrylate-based electrolyte has excellent high-voltage stability and is well compatible with high-voltage cathode materials.

[0051] Example 2

[0052] A preparation method and application of a perfluorinated polymer electrolyte and a solid-state battery, which are prepared by the following steps:

[0053] 1) Weigh 0.5 mL DFEC and 0.5 mL FEMC solvent and mix them evenly, add 0.5742 g LiTFSI (2M) and stir evenly.

[0054] 2) Add 8 wt% of 2,3,5,6-tetrafluorobutyl acrylate polymerization monomer by total weight of lithium salt and fluorine-containing organic solvent to the mixed solution, stir for 2 hours, then add 0.3 wt% of initiator AIBN, stir for 15 minutes to obtain a precursor solution.

[0055] 3) According to the assembly method of liquid lithium battery, the obtained precursor solution was added dropwise to the polypropylene (PP) separator, and the button battery was assembled. The button battery was left to stand for 2 hours, and then the battery was heated at 60°C for 12 hours to finally obtain a fully fluorinated solid polymer electrolyte lithium battery.

[0056] Example 3

[0057] A preparation method and application of a perfluorinated polymer electrolyte and a solid-state battery, which are prepared by the following steps:

[0058] 1) Weigh 1 mL of TFEC solvent, add 0.8613 g of LiTFSI (3 M) into it, and stir evenly.

[0059] 2) Add 10 wt% of 2,4,6-trifluorobenzyl methacrylate polymerization monomer in total weight of lithium salt and fluorine-containing organic solvent to the mixed solution, stir for 2 hours, then add 0.3 wt% of initiator AIBN, stir for 15 minutes to obtain a precursor solution.

[0060] 3) According to the assembly method of liquid lithium battery, the obtained precursor solution was added dropwise to the polypropylene (PP) separator, and the button battery was assembled. The button battery was left to stand for 2 hours, and then the battery was heated at 60°C for 12 hours to finally obtain a fully fluorinated solid polymer electrolyte lithium battery.

[0061] Example 4

[0062] A preparation method and application of a perfluorinated polymer electrolyte and a solid-state battery, which are prepared by the following steps:

[0063] 1) Weigh 1 mL of FEMC solvent and mix it evenly, add 0.2871 g of LiTFSI (1 M) into it, and stir evenly.

[0064] 2) Add 10 wt% of pentafluorobenzyl methacrylate polymerization monomer in total weight of lithium salt and fluorine-containing organic solvent to the mixed solution, stir for 2 hours, then add 0.3 wt% of initiator AIBN, stir for 15 minutes to obtain a precursor solution.

[0065] 3) According to the assembly method of liquid lithium battery, the obtained precursor solution was added dropwise to the polypropylene (PP) separator, and the button battery was assembled. The button battery was left to stand for 2 hours, and then the battery was heated at 60°C for 12 hours to finally obtain a perfluorinated polymer electrolyte lithium battery.

[0066] Example 5

[0067] A preparation method and application of a perfluorinated polymer electrolyte and a solid-state battery, which are prepared by the following steps:

[0068] 1) Weigh 1 mL of ETFEC solvent and mix evenly, add 0.2871 g of LiTFSI and stir evenly.

[0069] 2) Add 10 wt% of pentafluorophenyl acrylate polymerization monomer by total weight of lithium salt and fluorine-containing organic solvent to the mixed solution, stir for 2 hours, then add 0.3 wt% of initiator AIBN, stir for 15 minutes to obtain a precursor solution.

[0070] 3) According to the assembly method of liquid lithium battery, the obtained precursor solution was added dropwise to the polypropylene (PP) separator, and the button battery was assembled. The button battery was left to stand for 2 hours, and then the battery was heated at 60°C for 12 hours to finally obtain a perfluorinated polymer electrolyte lithium battery.

[0071] The inventors conducted comparative analysis on the ionic conductivity and electrochemical window of different polyfluorocyclic acrylate-based polymer electrolytes prepared in Examples 1-5. The results are shown in Table 1.

[0072] Table 1 Ionic conductivity and electrochemical window of polyfluorinated cyclic acrylate-based polymer electrolytes

[0073]

[0074] It can be seen that different polyfluorinated cyclic acrylate-based polymer electrolytes have excellent ionic conductivity (>10 -3 Scm -1) and a high upper limit of anti-oxidation voltage (>5.0V). This shows that the use of polyfluorinated cyclic acrylate as the polymer backbone, fluorinated groups and cyclic structures effectively improve the antioxidant properties of the electrolyte. In addition, the polyfluorinated cyclic acrylate backbone has excellent compatibility with fluorinated solvent molecules, and is conducive to the formation of an inorganic-rich interface layer on the electrode surface, achieving rapid ion migration.

[0075] Example 6

[0076] A preparation method and application of a perfluorinated polymer electrolyte and a solid-state battery, which are prepared by the following steps:

[0077] 1) Weigh 0.5 mL DFEC and 0.5 mL ETFEC solvent and mix them evenly, add 0.2871 g LiDFOB (1 M) and stir evenly.

[0078] 2) Add 8 wt% of the total weight of lithium salt and fluorine-containing organic solvent to the mixed solution, and stir for 4 hours. Then add 1 wt% of azobisisoheptanenitrile (C 14 H 24 N4) initiator, and stirred for 30 min to obtain a precursor solution.

[0079] 3) According to the assembly method of liquid lithium battery, the obtained precursor solution was added dropwise to the polypropylene (PP) separator, and the button battery was assembled. The button battery was left to stand for 2 hours, and then the battery was heated at 60°C for 30 hours to finally obtain a perfluorinated polymer electrolyte lithium battery.

[0080] Example 7

[0081] A preparation method and application of a perfluorinated polymer electrolyte and a solid-state battery, which are prepared by the following steps:

[0082] 1) Weigh 1 mL of FEC solvent and mix it evenly, add 0.2871 g of LiFSI (1 M) into it, and stir evenly.

[0083] 2) Add 9 wt% of the total weight of the lithium salt and the fluorine-containing organic solvent to the mixed solution, and stir for 2 hours. Then add 0.3 wt% of the initiator AIBN, and stir for 20 minutes to obtain a precursor solution.

[0084] 3) According to the assembly method of liquid lithium battery, the obtained precursor solution was added dropwise to the polypropylene (PP) separator, and the button battery was assembled. The button battery was left to stand for 1 hour, and then the battery was heated at 80°C for 24 hours to finally obtain a perfluorinated polymer electrolyte lithium battery.

[0085] Example 8

[0086] A preparation method and application of a perfluorinated polymer electrolyte and a solid-state battery, which are prepared by the following steps:

[0087] 1) Weigh 0.5 mL of FEC and 0.5 mL of ETFEC solvent and mix them evenly. Add 0.2871 g of (1M), stir well.

[0088] 2) Add 8 wt% of the total weight of lithium salt and fluorine-containing organic solvent to the mixed solution, and stir for 2 hours. Then add 0.8 wt% of azobisisoheptanenitrile (C 14 H 24 N4) initiator, and stirred for 30 min to obtain a precursor solution.

[0089] 3) According to the assembly method of liquid lithium battery, the obtained precursor solution was added dropwise to the polypropylene (PP) separator, and the button battery was assembled. The button battery was left to stand for 2 hours, and then the battery was heated at 70°C for 24 hours to finally obtain a fully fluorinated solid polymer electrolyte lithium battery.

[0090] Example 9

[0091] A preparation method and application of a perfluorinated polymer electrolyte and a solid-state battery, which are prepared by the following steps:

[0092] 1) Weigh 0.5 mL of FEC and 0.5 mL of FEMC solvent and mix them evenly, add 0.2871 g of LiFSI (1 M) and stir evenly.

[0093] 2) Add 10 wt% of the total weight of lithium salt and fluorine-containing organic solvent to the mixed solution, and stir for 2 hours. Then add 0.5 wt% of initiator AIBN, and stir for 15 minutes to obtain a precursor solution.

[0094] 3) According to the assembly method of liquid lithium battery, the obtained precursor solution was added dropwise to the polypropylene (PP) separator, and the button battery was assembled. The button battery was left to stand for 2 hours, and then the battery was heated at 60°C for 36 hours to finally obtain a fully fluorinated solid polymer electrolyte lithium battery.

[0095] Example 10

[0096] A preparation method and application of a perfluorinated polymer electrolyte and a solid-state battery, which are prepared by the following steps:

[0097] 1) Weigh 0.5 mL of FEC and 0.5 mL of FEMC solvent and mix them evenly, add 0.2871 g of LiTFSI (1 M) and stir evenly.

[0098] 2) Add 5 wt% of the total weight of lithium salt and fluorine-containing organic solvent to the mixed solution, stir for 2 hours, then add 0.3 wt% of initiator AIBN, stir for 30 minutes to obtain a precursor solution.

[0099] 3) According to the assembly method of liquid lithium battery, the obtained precursor solution was added dropwise to the polypropylene (PP) separator, and the button battery was assembled. The button battery was left to stand for 2 hours, and then the battery was heated at 60°C for 12 hours to finally obtain a perfluorinated polymer electrolyte lithium battery. The perfluorinated polymer electrolyte was named F1-GPE.

[0100] Fig. 9 is the ionic conductivity of the polymer electrolyte (F1-GPE) prepared with 5 wt% perfluorocyclohexyl methacrylate monomer. It can be found that the ionic conductivity of the perfluorocyclohexyl methacrylate-based electrolyte is 1.63×10 -3 S / cm, indicating that the perfluorocyclohexyl methacrylate-based electrolyte has excellent ion transport properties.

[0101] Fig.10 The lithium battery is assembled with lithium iron phosphate (LiFePO4) as the positive electrode and a polymer electrolyte (F1-GPE) prepared with 5wt% perfluorocyclohexyl methacrylate monomer. The battery can be charged at a rate of 1C (1C = 170 mAh g) in a voltage range of 2.5V to 4V. -1 ) is a cycle performance diagram. It can be found that after using perfluorocyclohexyl methacrylate-based electrolyte, its initial discharge specific capacity is 132.5 mAh g -1 After 20 cycles, the discharge capacity is 129.2 mAh g -1 The perfluorocyclohexyl methacrylate-based electrolyte has good cycling stability.

[0102] Fig.11 The lithium battery is assembled with the ternary material NCM811 as the positive electrode and a polymer electrolyte (F1-GPE) prepared with 5wt% perfluorocyclohexyl methacrylate monomer. The battery is charged at a rate of 0.2C (1C = 200mAh g) in the voltage range of 3V to 4.5V. -1 ) cycle specific capacity-voltage diagram. It can be found that after using perfluorocyclohexyl methacrylate-based electrolyte, its initial discharge specific capacity is 190.3 mAh g -1 After 20 cycles, the discharge capacity is 188.2 mAh g -1The perfluorocyclohexyl methacrylate-based electrolyte has good cycle stability, and its performance is similar to that of the perfluorocyclohexyl methacrylate-based polymer electrolyte (F-GPE) with 8 wt% total weight of lithium salt and fluorine-containing organic solvent added in Example 1, showing good uniformity.

[0103] Comparative Example

[0104] This is a preparation method and application of a polymer electrolyte and a solid-state battery using a PEGDA polymer monomer. As a comparative example, the preparation is performed by the following steps:

[0105] 1) Weigh 0.5 mL of FEC and 0.5 mL of FEMC solvent and mix them evenly, add 0.2871 g of LiTFSI (1 M) and stir evenly.

[0106] 2) Add 8 wt% of PEGDA monomer by total weight of lithium salt and fluorine-containing organic solvent to the mixed solution, stir for 2 hours, then add 0.3 wt% of initiator AIBN, stir for 30 minutes to obtain a precursor solution.

[0107] 3) According to the assembly method of liquid lithium battery, the obtained precursor solution was added dropwise to the polypropylene (PP) separator, and the button battery was assembled. The button battery was left to stand for 2 hours, and then the battery was heated at 60°C for 12 hours to finally obtain a perfluorinated polymer electrolyte lithium battery.

[0108] The above embodiments are merely examples for clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above descriptions. It is not necessary and impossible to list all the implementation methods here, and the obvious changes or modifications derived therefrom are still within the protection scope of the invention.

Claims

1. A perfluorinated polymer electrolyte material, characterized in that: The polyfluorocyclic acrylate monomer is obtained by initiating polymerization in a solvent system containing lithium salt and fluorine-containing organic solvent. The structural formula of the polyfluorocyclic acrylate monomer is shown in formula (I): (I) In formula (I): R1 is selected from H, methyl, ethyl or propyl; R2 is selected from a benzene ring or cyclic group containing fluorine atoms as shown in formula (II): (Ⅱ)。 2. The perfluorinated polymer electrolyte material according to claim 1, characterized in that: The polyfluorinated cyclic acrylate monomer is selected from one or more of 3-(2,4-difluorophenyl)methyl acrylate, 2,4,6-trifluorobenzyl methacrylate, 2,3,5,6-tetrafluorobutyl acrylate, pentafluorobenzyl methacrylate, and perfluorocyclohexyl methacrylate.

3. The perfluorinated polymer electrolyte material according to claim 1, characterized in that: The fluorine-containing organic solvent is selected from fluorocarbonate compounds, specifically at least one of fluoroethylene carbonate (FEC), bisfluoroethylene carbonate (DFEC), methyl trifluoroethyl carbonate (FEMC), bis (2,2,2-trifluoroethyl) carbonate (TFEC), and ethyl trifluoroethyl carbonate (ETFEC).

4. The perfluorinated polymer electrolyte material according to claim 1, characterized in that: The content of the polyfluorinated cyclic acrylate monomer is 3-15 wt% of the total weight of the lithium salt and the fluorine-containing organic solvent.

5. A method for preparing the perfluorinated polymer electrolyte material according to claim 1, characterized in that: The components including polyfluorocyclic acrylate, lithium salt and fluorinated organic solvent are uniformly stirred to obtain a precursor solution, and the precursor solution is subjected to a thermal polymerization reaction under the action of an initiator to obtain a polymer electrolyte containing polyfluorocyclic acrylate. The steps specifically include: 1) Under an argon protective atmosphere, dissolving a lithium salt in an organic solvent to obtain a mixed solution; 2) Adding a polyfluorocyclic acrylate monomer to the mixed solution obtained in step 1); 3) Add an initiator to the mixed solution obtained in step 2) and disperse it evenly to obtain a precursor solution. 4) Heating at a certain temperature until the polymerizable monomers are completely polymerized to form a polymeric electrolyte. The conditions for the thermally initiated polymerization reaction are: a polymerization temperature of 40 to 80° C. and a polymerization time of 6 to 60 hours.

6. The perfluorinated polymer electrolyte material according to claim 5, characterized in that: The lithium salt is selected from at least one of lithium hexafluorophosphate (LiPF6), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium tetrafluoroborate (LiBF4), and lithium difluorooxalatoborate (LiDFOB), and the concentration is 0.5-3 mol / L.

7. The perfluorinated polymer electrolyte material according to claim 5, characterized in that: The initiator is selected from azobisisobutyronitrile (AIBN), azobisisoheptanenitrile (C 14 H 24 N4), the content of which accounts for 0.3-1 wt% of the total weight of the polyfluorocyclic acrylate monomer, the lithium salt and the fluorine-containing organic solvent.

8. Use of the perfluorinated polymer electrolyte according to claim 1 as a lithium ion battery electrolyte material for assembling a lithium ion battery.

9. The use according to claim 8, characterized in that: The assembly method is: according to the assembly method of liquid lithium battery, the obtained precursor solution is dripped into the diaphragm, and the battery is assembled with the positive electrode and the negative electrode, and then placed at a certain temperature for heating, and the polymerization monomer is completely polymerized and a polymer electrolyte is formed inside the battery, so as to obtain a fully fluorinated solid polymer electrolyte lithium battery, wherein: the conditions of the thermally initiated polymerization reaction are: the polymerization temperature is 40 to 80°C, and the polymerization time is 6 to 60 hours.

10. A Li||NCM811 battery or a LiFePO4||Li battery assembled using the perfluorinated polymer electrolyte material according to claim 1 as a lithium ion battery electrolyte material.

Citation Information

Patent Citations

  • Solid polymer electrolyte and lithium secondary battery comprising same

    CN109565077A

  • Polymer electrolyte as well as preparation method and application thereof

    CN114400374A

  • Electrolyte, preparation method thereof and sodium ion battery

    CN116742125A

  • Preparation method of negative pole piece, negative pole piece and battery

    CN116779787A

  • Fluorine-containing acrylate copolymer, adhesive, protective film and application thereof

    CN117756977A

Cited By

  • Preparation method and application of in-situ polymerization solid-state composite electrolyte

    CN121688077A